Hierarchical Self‐Assembly of a Dandelion‐Like Supramolecular Polymer into Nanotubes for use as Highly Efficient Aqueous Light‐Harvesting Systems. (8th September 2016) - Zhang, Dapeng; Liu, Yannan; Fan, Yujiao; Yu, Chunyang; Zheng, Yongli; Jin, Haibao; Fu, Li; Zhou, Yongfeng; Yan, Deyue
Abstract : A dandelion‐like supramolecular polymer (DSP) with a "sphere‐star‐parachute" topological structure consisting of a spherical hyperbranched core and many parachute‐like arms is constructed by the non‐covalent host–guest coupling between a cyclodextrin‐endcapped hyperbranched multi‐arm copolymer (host) and many functionalized adamantanes with each having three alkyl chain arms (guests). The obtained DSPs can further self‐assemble into nanotubes in water in a hierarchical way from vesicles to nanotubes through sequential vesicle aggregation and fusion steps. The nanotubes have a bilayer structure consisting of multiple "hydrophobic‐hyperbranched‐hydrophilic" layers. Such a structure is very useful for constructing a chlorosome‐like artificial aqueous light‐harvesting system, as demonstrated here, via the incorporation of hydrophobic 4‐(2‐hydroxyethylamino)‐7‐nitro‐2, 1, 3‐benzoxadiazole as donors inside the hyperbranched cores of the nanotubes and the hydrophilic Rhodamine B as the acceptors immobilized on the nanotube surfaces. This as‐prepared nanotube light harvesting system demonstrates unexpectedly high energy transfer efficiency (above 90%) in water. This extends supramolecular polymers with more complex topological structure, special self‐assembly behavior, and new functionality. Abstract : A dandelion‐like supramolecular polymer is constructed through the host–guest coupling between cyclodextrin‐functionalized hyperbranched multi‐arm polymer and adamantane functionalized organic molecule with three dodecyl chains. It can self‐assemble into nanotubes in water. The nanotubes display great potential for construction of a chlorosome‐like aqueous light‐harvesting system with high energy transfer efficiency (above 90%) by incorporating specific donors inside and acceptors on the surface.